Rudogorites simonei gen. nov. and sp. nov. from Central Bosnia (Coleoptera: Leiodidae: Cholevinae: Leptodirini) - Polak, Slavko; Mulaomerović, Jasminko (Zootaxa, 2021)
Dinaric karst in Western Balkans is especially biodiverse in cave beetle fauna. Despite the territory of Bosnia and Herzegovina being a relatively well-studied region, new species are still discovered and described regularly, even in recent times. Discoveries of new genera are, however, rare. Based on recently collected beetle specimens in the cave Lijina Pećina near the town of Kreševo in the region of Bosansko Rudogorje in Central Bosnia, a new troglobiotic leptodirine genus Rudogorites gen. nov. and a single new species R. simonei sp. nov. are described. The region of Bosansko Rudogorje consists mainly of non-carbonate rocks, sandstones and polymetallic ore. In the area, there is a patch of isolated karst where a new endemic subterranean fauna has been found. An updated key to the Leptodirini genera of the Apholeuonus phyletic group is provided.